IgE antibodies in relation to prevalence and multimorbidity of eczema, asthma, and rhinitis from birth to adolescence. Issue 3 (22nd December 2015) - Ballardini, N.; Bergström, A.; Wahlgren, C‐F.; van Hage, M.; Hallner, E.; Kull, I.; Melén, E.; Antó, J. M.; Bousquet, J.; Wickman, M.
Abstract: Background: Eczema, asthma, and rhinitis affect a large proportion of children, but their prevalence varies with age. IgE antibodies are also common in the pediatric population. However, the links between IgE, disease, and trajectories are unclear. Objective: To better understand the links between sensitization and disease, we studied IgE sensitization ever in relation to eczema, asthma, and rhinitis, in children followed up to 16 years of age. Methods: From the Swedish population‐based birth cohort BAMSE, 2607 children were included. Parental reports from six time points between 1 and 16 years were used to identify children with eczema, asthma, and rhinitis. Blood was collected at 4, 8, and 16 years, and sensitization ever was defined as allergen‐specific IgE ≥0.35 kUA /l to common food and/or inhalant allergens at any time point. Odds ratios for eczema, asthma, rhinitis, and multimorbidity in relation to sensitization ever were calculated using generalized estimating equations. Results: Fifty‐one percent were sensitized at least once up to 16 years. Almost a quarter of ever‐sensitized children did not have any disease. After adjustment for potential confounders, sensitization ever was significantly associated with the following: (i) eczema throughout childhood, (ii) multimorbidity of eczema, asthma, and rhinitis from 1 to 16 years (OR for multimorbidity: 5.11, 95% CI: 3.99–6.55), (iii) asthma and rhinitis from 4 to 16 years of age. Conclusions: Specific IgE is strongly associated with eczema and allergic multimorbidity throughout childhood and with asthma and rhinitis from age 4 years. However, 23% of the children with IgE sensitization do not develop any disease in childhood.